2017
DOI: 10.2166/ws.2017.193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of invertebrate removal by traditional-BAC and pre-BAC treatment processes: verification in a full-scale drinking water treatment plant

Abstract: Invertebrate removal by traditional biological activated carbon (tra-BAC) and pre-BAC treatment processes was investigated in a full-scale water treatment plant. The results showed that invertebrate reproduction occurred in both BAC filters, but the invertebrate abundance in the finished water processed by tra-BAC was about 15 times greater than that processed using the pre-BAC process. In the pre-BAC process, the sand filter was placed after the BAC filter, and sand filtration removed most of the invertebrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The problems associated with occurrence of invertebrates in drinking water have received increasing attention in recent years. The occurrence of visible invertebrates in tap water causes psychological discomfort to consumers and decreases consumer confidence in tap water quality [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In addition, it can lead to indirect negative effects such as microbial regrowth [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The problems associated with occurrence of invertebrates in drinking water have received increasing attention in recent years. The occurrence of visible invertebrates in tap water causes psychological discomfort to consumers and decreases consumer confidence in tap water quality [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In addition, it can lead to indirect negative effects such as microbial regrowth [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of visible invertebrates in tap water causes psychological discomfort to consumers and decreases consumer confidence in tap water quality [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. In addition, it can lead to indirect negative effects such as microbial regrowth [ 11 , 12 ]. In the case of benthic macroinvertebrates, most of these are eliminated during the filtration of the surface water, but it has been reported that some remain in the GAC or biological activated carbon (BAC) filter layer and can survive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation